Mediators of Sexual Functioning and Marital Quality in Chronically Depressed Adults with and Without a History of Childhood Sexual Abuse. (20th October 2014) - Dunlop, Boadie W.; Hill, Eric; Johnson, Benjamin N.; Klein, Daniel N.; Gelenberg, Alan J.; Rothbaum, Barbara O.; Thase, Michael E.; Kocsis, James H.
Abstract Introduction Sexual dysfunction is common among depressed adults. Childhood sexual abuse (CSA) and depressive symptomology are among the risk factors for sexual dysfunction, and these factors may interact to predict adult relationship functioning. Several models have been developed postulating interactions between these variables. Aim We tested models of the effects of CSA and elucidate the associations between CSA, sexual dysfunction, depression severity, anxiety, and relationship quality in chronically depressed adults. Methods Baseline data from 808 chronically depressed outpatients enrolled in the Research Evaluating the Value of Augmenting Medication with Psychotherapy study were evaluated using structural equation modeling. Main Outcome Measures The Inventory of Depressive Symptomology, self‐report version (IDS‐SR) assessed depression severity, and the Mood and Anxiety Symptom Questionnaire Anxious Arousal subscale assessed anxiety. Sexual function was assessed with the Arizona Sexual Experiences Scale (ASEX), and the Quality of Marriage Index (QMI) assessed relationship quality for patients in stable relationships. Results CSA scores predicted depression severity on the IDS‐SR, as well as lower relationship quality and sexual satisfaction. ASEX scores were significantly associated with depression severity but were not correlated with the QMI. Two models were evaluated to elucidate these associations, revealing that (i) depression severity and anxious arousal mediated the relationship between CSA and adult sexual function, (ii) anxious arousal and sexual functioning mediated the association between CSA and depression symptoms, and (iii) when these models were combined, anxious arousal emerged as the most important mediator of CSA on depression which, in turn, mediated associations with adult sexual satisfaction and relationship quality. Conclusions Although CSA predicts lower relationship and sexual satisfaction among depressed adults, the long‐term effects of CSA appear to be mediated by depressive and anxious symptoms. It is important to address depression and anxiety symptoms when treating patients with CSA who present with sexual dysfunction or marital concerns. Dunlop BW, Hill E, Johnson BN, Klein DN, Gelenberg AJ, Rothbaum BO, Thase ME, and Kocsis JH. Mediators of sexual functioning and marital quality in chronically depressed adults with and without a history of childhood sexual abuse. J Sex Med 2015;12:813–823.